1978
DOI: 10.1002/food.19780220809
|View full text |Cite
|
Sign up to set email alerts
|

Succinic Acid in Yeast Autolysates and its Sensory Properties

Abstract: Succinic acid content of 6 samples of yeast autolysates. ponders and pastes, was determined being 66 t o 1390 mg/roo g. Succinic acid solutions of various concentrations and p H were prepared t o gain fundamental informations about its sensory properties and the intensities of sour, salty and bitter taste were organoleptically evaluated. I n other experiments, aqueous solutions of monosodium glutamate and sodium succinate were compared and the influence of the t\vo salts on flavour of beef broth was tested. I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…As shown in Table , only umami Glu and succinate having a sensory‐activity for TAV of >1.0 was calculated, whereas the individual contribution of other compounds in the yeast extract to the basic taste was limited. The result presented here also showed that Glu and succinate were the main umami substances in the yeast extract, which was in accordance with earlier reports . It has long been known that some amino acids could impart a bitter taste to foodstuffs .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Table , only umami Glu and succinate having a sensory‐activity for TAV of >1.0 was calculated, whereas the individual contribution of other compounds in the yeast extract to the basic taste was limited. The result presented here also showed that Glu and succinate were the main umami substances in the yeast extract, which was in accordance with earlier reports . It has long been known that some amino acids could impart a bitter taste to foodstuffs .…”
Section: Resultssupporting
confidence: 92%
“…The result presented here also showed that Glu and succinate were the main umami substances in the yeast extract, which was in accordance with earlier reports. 7 It has long been known that some amino acids could impart a bitter taste to foodstuffs. 24 However, the calculation of TAVs of six bitter amino acids revealed that the concentrations of these compounds were below their taste threshold concentrations, and could be excluded as important taste contributors to the bitter taste.…”
Section: Sensory Addition Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Umami substances are naturally found in a wide variety of foods, such as meat, cheese, seafood and vegetables (Chaudhari, Pereira, & Roper, 2009;Drake et al, 2007;Nishimura, 1998;Velíšek, Davidek, Kubelka, Thu, & Hajšlová, 1978;Yamaguchi & Ninomiya, 1999). Numerous peptides, generated by enzymatic hydrolysis or fermentation from plant and animal proteins, have also been reported to elicit intense umami taste (Lioe, Takara, & Yasuda, 2006;Schlichtherle-Cerny & Amadò, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…More than 40 years ago [2 -4], a first flavor synergism was reported between the umami-like tasting monosodium L-glutamate and purine-59-ribonucleotides which occur in savory foods such as meat, fish, seafood, and mushrooms, and are widely used as ingredients to enhance the flavor and mouthfeel of culinary products, snacks, soups, and seasonings. Apart from L-glutamic acid, its lower homologue L-aspartic acid as well as the C 4 -dicarboxylic acids succinic acid and tartaric acid exhibit some kind of umami taste [5,6]. In addition, lactic acid was found to contribute to the glutamate-like taste of foods such as beef bouillon and stewed beef juice [7,8].…”
Section: Introductionmentioning
confidence: 99%